(untitled) (English Language Teaching Perspectives, 2024)
Professional development for English language teachers is the process of becoming professionally competent in the classroom and keeping up with the most recent advancements in teaching and learning. In this context, this study explores the factors that influence the secondary level English language teachers’ professional development. Employing the phenomenological research design, four English language teachers were purposively selected from four community schools of Kailali district. Semi-structured interviews and open-ended questions were used as the tools of data collection. The participants were provided open-ended questions to collect information and later on, semi-structured interviews were conducted with each participant for supplementary information. The study reveals that for the professional enhancement of teachers, it is essential to provide sufficient time, resources, chances to attend workshops, equal treatment to all staff, collaboration, support, encouragement, incentive and feedback from administration, peers and students. The findings suggest that since professional development is crucial for improving pedagogical skills and keeping up with current educational trends, English language teachers need institutional, financial, social, and psychological supports.